Phenotypic and genotypic characterisation of drug-resistant Plasmodium vivax. - Price, R; Auburn, S; Marfurt, J; Cheng, Q (2012)
In this review we present recent developments in the analysis of Plasmodium vivax clinical trials and ex vivo drug-susceptibility assays, as well approaches currently being used to identify molecular markers of drug resistance. Clinical trials incorporating the measurement of in vivo drug concentrations and parasite clearance times are needed to detect early signs of resistance. Analysis of P. vivax growth dynamics ex vivo have defined the criteria for acceptable assay thresholds for drug susceptibility testing, and their subsequent interpretation. Genotyping and next-generation sequencing studies in P. vivax field isolates are set to transform our understanding of the molecular mechanisms of drug resistance.